Flexural Bending and Fatigue Analysis of Functionally Graded Viscoelastic Materials: Experimental and Numerical Approaches - Njim, E.K.; Sadiq, S.E.; Tahir, M.S. Al-Din; Flayyih, M.A.; Hadji, L. (Physics and Chemistry of Solid State, 2023)
This work synthesized a thermoplastic polymer with varying densities along one direction using additive manufacturing technology to study the dynamic and static characteristics of functionally graded viscoelastic materials (FGVMs). To describe the mechanical properties of FGVMs, an analytical formulation based on the sigmoid-law formulation was proposed. The experimental program is conducted on 3D-printed samples, and various tests are conducted to examine the performance of such materials. Furthermore, the finite element method was used to evaluate the structural system's flexural properties. The influences of FG parameters and geometrical properties on flexural and reverse bending fatigue life are analyzed. The results show that increasing porosity from 10% to 30% at a power-law index (k = 2) reduces bending strength by 31.25 percent and deflection by around 11.2 percent for VE samples. Changing the power-law exponent from 0.5 to 10 increases fatigue strength by 35 %.